Giving a Voice to the Unheard: Latinx Attitudes, Decision-Making, and Experiences With Abortion [A25]. (May 2022) - Urbina, Josephine; Rivas, Mercedes Posadas; Kerns, Jennifer; Steinauer, Jody
Abstract : INTRODUCTION: While Latinas make up 25% of abortion patients in the US, they are poorly represented in abortion studies. This gap in information has contributed to an inadequate understanding of Latinx pregnancy-related decision making. The goal of this ethnically and language-concordant study was to qualitatively examine how Latinx women feel about abortion and their decision-making path in order to provide the community with equitable and quality care, outcomes, and experiences. METHODS: We recruited English- and Spanish-speaking Latinx women from the five US cities with the largest Latinx populations. After screening participants online, we invited a diverse pool to participate in one-on-one interviews to examine their attitudes, decision-making, and experiences with abortion. We utilized a community advisory board of Latinx women to provide insight into the development of the interview guide. Using thematic analysis, we analyzed transcripts iteratively, identifying themes from interviews; we stopped recruitment when we reached thematic saturation. RESULTS: We conducted 30 interviews, and participants described mixed experiences. Three overarching themes from the qualitative interviews were: shame and/or stigma, cultural humility, and access to abortion. Most participants described providers not understanding their culture as a larger barrier than providers not speaking their language. In addition, participants identified family and culture as the most influential factors on their beliefs about abortion. Religion was mentioned less frequently. CONCLUSION: Latinx attitudes and decision-making surrounding abortion is not monolithic. Abortion care delivery should be individualized and efforts should continue to assess the cultural and linguistic relevance of how services are delivered to the Latinx community.